2016
DOI: 10.1371/journal.pone.0164741
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Environmental Factors on Low Weight in Non-Premature Births: A Time Series Analysis

Abstract: ObjectiveExposure to pollutants during pregnancy has been related to adverse birth outcomes. LBW can give rise to lifelong impairments. Prematurity is the leading cause of LBW, yet few studies have attempted to analyse how environmental factors can influence LBW in infants who are not premature. This study therefore sought to analyse the influence of air pollution, noise levels and temperature on LBW in non-premature births in Madrid during the period 2001–2009.MethodsEcological time-series study to assess the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
48
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(50 citation statements)
references
References 58 publications
1
48
0
1
Order By: Relevance
“…Low birth weight at the time of delivery relative to gestational age was examined by five studies [ 33 , 34 , 37 , 38 , 39 ]. Of those studies, all five addressed heat outcomes [ 33 , 34 , 37 , 38 , 39 ]; three of five found significant correlations of increased heat exposure and low birth weight [ 34 , 37 , 38 ]. Seven studies examined the general effect of decreased birthweight as a result of ambient temperature exposure [ 31 , 34 , 35 , 38 , 40 , 41 , 42 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Low birth weight at the time of delivery relative to gestational age was examined by five studies [ 33 , 34 , 37 , 38 , 39 ]. Of those studies, all five addressed heat outcomes [ 33 , 34 , 37 , 38 , 39 ]; three of five found significant correlations of increased heat exposure and low birth weight [ 34 , 37 , 38 ]. Seven studies examined the general effect of decreased birthweight as a result of ambient temperature exposure [ 31 , 34 , 35 , 38 , 40 , 41 , 42 ].…”
Section: Resultsmentioning
confidence: 99%
“…Inflammation may also contribute to low birth weight or preterm birth [ 58 ]. Díaz et al [ 39 ] argue that preterm birth and low birth weight outcomes must be considered separately due to the high correlation between preterm birth and low birthweight. Socioeconomic factors may further play a role, as psychological stress, social stress, and housing instability may further increase risk for preterm birth [ 58 , 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…Mechanisms for maternal PM 2.5 exposure on birth weight are poorly understood at present, but several responses speculated by researchers seem to be involved: systemic oxidative stress, endothelium dysfunction, pro-inflammation and pro-thrombosis of lung or placenta after being inhaled and reaching the blood circulation of humans [58]. The development and maintenance of sufficient uteroplacental circulation in the mother is an essential circumstance for fetal growth [1,59].…”
Section: Discussionmentioning
confidence: 99%
“…The relative risk of Leqd on low birth weight was 1.09 (95 CI: 0.99–1.19) ( p < 0.1). Leqd, however, displayed an appreciably higher AR than that of PM, i.e., around 8%, though this was exclusively for the variable, low birth weight, and this increase in risk was significant at only p < 0.1 [ 23 ]. No association was reported for VLBW and ELBW.…”
Section: Road Traffic Noisementioning
confidence: 99%